Islam dan Persaudaraan Antaragama: Dari Kesadaran Individu Menuju Kesadaran Sosial - Masykur Arif ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2015)
Islam is a religion that brings blessing and prosperity for all the rest of world (rahmatan lil alamin). The moral message of peace and brotherhood is included into a sacred text Al-Quran and embedded into the long history of this religion. The idea of brotherhood is also central for peace building, even among religious believers. The history of religion has showed that every religion reflects double masks of human: peaceful and anger, god and evil. However, such double identity was born from single transcendental vision: getting blessed by God. This study attempts to explore this double mask of religion because of the multi-interpreted sacred texts of any religion in the world. Given the essence of religion for peace of all the rest of world, the believers have to be aware of understanding religion in terms of its humanity, not animality. The implication of this study is to figure out that an attempt of getting Islam back to its vital essence of peace-builder is not being easy, but must be started as Mohammad’s moral message of the importance of peace and brotherhood.